Penggunaan Platform Genially dan Pengaruhnya Terhadap Hasil Belajar Mata Pelajaran PAI Di SMK Negeri 2 Semarang - Alza Nabiel Zamzami; Raharjo Raharjo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the influence of the Genially Platform on PAI learning outcomes at SMK Negeri 2 Semarang. The type of research used is field research with a quantitative approach. Data collection methods use observation, tests and documentation. This research design uses an experimental posttest only control design, with different treatments in two classes, namely the experimental class using the Genial platform and the control class using conventional learning. After being given different treatments, analysis prerequisite tests were carried out, namely data normality tests, data homogeneity tests, and hypothesis tests. In testing the hypothesis, researchers used the independent sample t-test.